Roland Mellor, Tacitus, New York-London, Routledge, 1993, XII + 212 pp. ISBN 0-415-90665-2 (Minerva, 2019)
Review: Roland Mellor, Tacitus, New York-London, Routledge, 1993, XII + 212 pp. ISBN 0-415-90665-2